(untitled) (Raparin Journal of Humanities (RJH), 2021)
This paper is about ‘An Economic Perspective on Language Management in Iraqi Kurdistan’. In many languages the relationship between the economy and the language is seriously taken into consideration. Unfortunately, Kurdish language is in a critical situation in this respect. This paper tries to show the linguistic situation of Kurdish language from the economic perspective through studying the related concepts such as language economics, language investment, language industry and its relation to language planning and language policy. Aiming at drawing some of the possible aspects through which there could be a space for investment in the Kurdish language, this study also searches for coming across some current cases of linguistic investment in different parts of the world such as Britain, France and Canada. Meanwhile, it focuses on most outstanding obstacles that stand against the process of investment in Kurdish which includes the lack of awareness, the non-stimulating regulatory besides investment environment, and the unstable economic and linguistic situations in the region. The study comes to conclude that many countries had invested in language considerably to improve this aspect to pave the way for acquiring huge, direct and indirect economic revenues. As much as investors care about English, they need to care about Kurdish. Hereby, there is a crucial need to support experimental studies to reveal the potentials of investing in Kurdish to indicate the existing deficiencies regarding the effective language investment situations.